2017
DOI: 10.1111/anae.13968
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metrics-based feedback on acquisition of sonographic skills relevant to performance of ultrasound-guided axillary brachial plexus block

Abstract: The objective of this study was to examine the effect of metrics-based vs. non-metrics-based feedback on novices learning predefined competencies for acquisition and interpretation of sonographic images relevant to performance of ultrasound-guided axillary brachial plexus block. Twelve anaesthetic trainees were randomly assigned to either metrics-based-feedback or non-metrics-based feedback groups. After a common learning phase, all participants attempted to perform a predefined task that involved scanning the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“… 20 It has been shown that these sonographic skills were performed more successfully by anesthesia trainees when they were provided with expert-guided feedback. 21 Although we do not recommend YouTube videos as a learning tool as per our findings, publishing recordings of these modern regional anesthesia training videos together with explanatory feedback points may help watchers to understand the steps and errors made by trainees. These videos when made by reputable medical institutes might be quite beneficial for regional anesthesia trainees or residents.…”
Section: Discussionmentioning
confidence: 77%
“… 20 It has been shown that these sonographic skills were performed more successfully by anesthesia trainees when they were provided with expert-guided feedback. 21 Although we do not recommend YouTube videos as a learning tool as per our findings, publishing recordings of these modern regional anesthesia training videos together with explanatory feedback points may help watchers to understand the steps and errors made by trainees. These videos when made by reputable medical institutes might be quite beneficial for regional anesthesia trainees or residents.…”
Section: Discussionmentioning
confidence: 77%
“…It has been shown that education taught on non-ideal, real-world patients and not healthy volunteers can increase the efficacy of learning [17]. In addition, novices' sonographic skills showed greater improvement when feedback was combined with validated met- rics [1]. Systematic reviews have shown that simulation-based training in health care is significantly more effective than alternative teaching methods or no intervention [7].…”
Section: Discussionmentioning
confidence: 99%
“…The PBP approach to training is based on solid research and has been validated in different healthcare settings for over a decade [e.g., laparoscopic (11)(12)(13), arthroscopic (20,21), robotic (22), endovascular skills (23), anesthetic (24)(25)(26), mechanical thrombectomy for ischemic stroke (5), and communication skills (27)]. Results from the first multicenter randomized prospective trial of proficiency-based progression simulation training (for an arthroscopic shoulder procedure) showed that intra-operative errors were reduced by 56% when compared to the standard approach to training (21).…”
Section: A Scientific Approach To Trainingmentioning
confidence: 99%